Implementation of agroforestry system for improved performance and sustainability of coffee farming in west Lampung regency, Indonesia - Prasmatiwi, Fembriarti Erry; Endaryanto, Teguh; Seta, Amanda Putra; Evizal, Rusdi; Astuti, Tri Novi (Edelweiss Applied Science and Technology, 2025)
The global coffee industry, including in Indonesia, faces economic and environmental sustainability challenges, with low productivity and negative impacts of climate change. Although agroforestry systems can be a solution to address these challenges, the adoption of agroforestry practices among farmers is still low. This study aims to analyze the performance and sustainability of coffee farming by comparing three farming systems: coffee monoculture system (CMS), simple agroforestry system (SAFS), and complex agroforestry system (CAFS), and formulate strategies to improve the sustainability of coffee farming. A survey approach involving 210 coffee farmers in two sub-districts in West Lampung assessed farm performance based on farm productivity and income. Sustainability was analyzed using the Multi-Aspect Sustainability Analysis (MSA) method. The results showed that CAFS significantly improved coffee farming performance. The sustainability analysis showed that the sustainability value of coffee farming in West Lampung Regency with CAFS (60.20) shows the highest sustainability value compared to SAFS (57.39) and CMS (53.80). These findings confirm that agroforestry implementation elevates coffee farming's sustainability value. Key improvement strategies target multiple factors: enhanced land conservation, road access, increased capital availability, improved market access, higher productivity, strengthened safety and security, microfinance institution development, corporate cooperation, quality seedlings, and advanced harvesting techniques.